Factors for formal help-seeking among female survivors of intimate partner violence - Cho, Hyunkag (Journal of family violence, 2021)
Intimate partner violence (IPV) results in numerous negative physical and mental health consequences. Research shows that many factors affect survivors’ help-seeking decisions. Previous studies were limited by small samples, and by excluding multiple forms of IPV consequences and multiple types of help sources. This study attempted to fill this gap by using a nationally representative dataset that collected data on multiple consequences of violence and formal sources of help. This study used the National Crime Victimization Survey to examine factors for female survivors’ help-seeking (n = 474). The main variables were formal help-seeking (medical, legal), types of victimization and consequences, and demographics. All were examined through logistic regression analyses. Black/African American survivors sought more formal help than their White counterparts. Sexually victimized survivors used less legal help than those victimized by physical violence. These results suggest that survivors’ formal help-seeking should be viewed in a broad health context, including their experienced victimization, subsequent medical needs, and the circumstances and conditions underlying their decision to seek a particular type of help. Future research needs to examine the circumstances and outcomes of both formal and informal help-seeking by racial/ethnic minorities. Law enforcement officers may be able to collaborate with medical care systems to ensure that survivors receive proper treatment. Future research is needed to better understand survivors’ help-seeking as navigating through complicated webs of their experienced victimization, subsequent medical needs, and the circumstances and conditions underlying their decision to seek which type of help.